KECEPATAN EFEKTIF MEMBACA SISWA KELAS X SMAN 1 PUNGGUR KABUPATEN LAMPUNG TENGAH - Eva Sartika Sari; Siti Samhati; Wini Tarmini (FKIP Universitas Lampung, 2013)
Problems studied were effective speed reading class X SMA Negeri 1 Punggur Lampung Tengah regency school year 2012/2013. This study aims to describe the effective speed reading (hereinafter referred to KEM) students who have a term of words per minute (wpm). The effective speed reading involves two things, namely the speed of reading and comprehension. The method used in this research is descriptive method. Readability formulas used to estimate the level of difficulty or readability discourse in this research that uses charts and graphs raygor fry. Charts and graphs raygor fry is the result of an effort to simplify and streamline the readability level of discourse.The study population was all students in the class X SMA Negeri 1 Punggur Lampung Tengah regency school year 2012/2013 amounted to 254 students spread in seven classes.Keywords: speed reading, reading comprehension, effective speed reading